Well-being issues: Its influence on RPE and enjoyment in masters water polo training and the player–coach gap - Corrado Lupo; Damiano Li Volsi; Paolo Riccardo Brustio; Alexandru Nicolae Ungureanu (PLoS ONE, 2026)
The present study aimed to monitor male master water polo players’ training by means of well-being (Hooper-Index), internal training load (ITL) parameters (rating of perceived exertion, RPE; session-RPE), and rate of enjoyment, for different types of training (i.e., swimming, SW; technical and tactical, TTW; training matches, TM; friendly matches; FM). Seventeen male master water polo players (age: 50 ± 12 years) performed 19 ± 7 sessions and reported Hooper-Index scores in the morning of training day, and RPE (CR-10) and rate of enjoyment after sessions. Linear mixed effects models were applied to quantify whether players’ RPE, session-RPE, and rate of enjoyment were: (i) different for type of training session, (ii) affected by pre-session well-being, and (iii) correlated to corresponding coach’s estimations. FM was the training type with the highest session-RPE (p < 0.001, ES range = 1.4–1.9), whereas SW reported the lowest rate of enjoyment (p < 0.05, ES range = 0.8–1.4). Similar effects emerged for coach’s estimations (the highest session-RPE in FM, p < 0.001, ES range = 1.4–2.1; the lowest rate of enjoyment in SW, p < 0.001, ES range = 3.2–5.3). RPE resulted affected by all well-being factors excepting sleep quality (β range = 0.16–0.28), whereas session-RPE was influenced only by fatigue, and Hooper-Index overall (β = 0.23) and no effect emerged for rate of enjoyment. Finally, players’ and coach’s ITL and rate of enjoyment were not correlated, with exception of TM session-RPE (β = 0.21). Master water polo coaches could benefit from these findings, being aware of how training load could be: different for types of workouts, influenced by pre-session well-being, and differently perceived by players if compared with their coach’s estimations.